Elvesztett jelentés, avagy ahol a fordító kompetenciája véget ér - Teleki, Anna (Studia Litteraria, 2020)
The paper analyses a short story from one of the best known representatives of the Russian new realist literature, Roman Senchin’s “A Real Man” (“Nasztojascsij pareny”), and it also examines the experiences of the Hungarian translator in connection with its translation. The article focuses on the loss of meaning which is generated by the differences between the two distinct cultures, despite the best efforts of the translator. The Senchin text poses a near impossible task for the translator because of its intertextual connections with the Russian cult film, Brother, together with the untranslatable cultural codes in the film.